Relaxation kinetics following sudden Ca(2+) reduction in single myofibrils from skeletal muscle. - Tesi, Chiara (2002)
To investigate the roles of cross-bridge dissociation and cross-bridge-induced thin filament activation in the time course of muscle relaxation, we initiated force relaxation in single myofibrils from skeletal muscles by rapidly (approximately 10 ms) switching from high to low [Ca(2+)] solutions. Full force decay from maximal activation occurs in two phases: a slow one followed by a rapid one. The latter is initiated by sarcomere "give" and dominated by inter-sarcomere dynamics (see the companion paper, Stehle, R., M. Krueger, and G. Pfitzer. 2002. Biophys. J. 83:2152-2161), while the former occurs under nearly isometric conditions and is sensitive to mechanical perturbations. Decreasing the Ca(2+)-activated force preceding the start of relaxation does not increase the rate of the slow isometric phase, suggesting that cycling force-generating cross-bridges do not significantly sustain activation during relaxation. This conclusion is strengthened by the finding that the rate of isometric relaxation from maximum force to any given Ca(2+)-activated force level is similar to that of Ca(2+)-activation from rest to that given force. It is likely, therefore, that the slow rate of force decay in full relaxation simply reflects the rate at which cross-bridges leave force-generating states. Because increasing [P(i)] accelerates relaxation while increasing [MgADP] slows relaxation, both forward and backward transitions of cross-bridges from force-generating to non-force-generating states contribute to muscle relaxation.